Racial/Ethnic Differences in Drug- and Alcohol-Related Arrest Outcomes in a Southwest County From 2009 to 2018 - Camplain, Ricky (Am J Public Health, 2020)
Objectives. To estimate the association between race/ethnicity and drug- and alcohol-related arrest outcomes. Methods. We used multinomial logistic regression and general estimating equations to estimate the association between race/ethnicity and arrest outcomes in 36 073 drug- and alcohol-related arrests obtained from administrative records in a Southwest US county from 2009 to 2018. Results were stratified by charge type. Results. Among misdemeanor drug- and alcohol-related arrests, American Indian/Alaska Native (AI/AN; adjusted odds ratio [AOR] = 3.60; 95% confidence interval [CI] = 3.32, 3.90), Latino (AOR = 1.53; 95% CI = 1.35, 1.73), and Black persons (AOR = 1.28; 95% CI = 1.05, 1.55) were more likely than White persons to be booked into jail as opposed to cited and released. AI/AN (AOR = 10.77; 95% CI = 9.40, 12.35), Latino (AOR = 2.63; 95% CI = 2.12, 3.28), and Black persons (AOR = 1.84; 95% CI = 1.19, 2.84) also were more likely than White persons to be convicted and serve time for their misdemeanor charges. Results were similar for felony drug- and alcohol-related arrests aggregated and stratified. Conclusions. Our results suggest that race/ethnicity is associated with outcomes in drug-related arrests and that overrepresentation of racial/ethnic minorities in the criminal justice system cannot be attributed to greater use of drugs and alcohol in general.